Pengaruh Kesejahteraan Psikologis Dan Kontrak Psikologis Terhadap Keterikatan Kerja Karyawan - Maya Sari, Fera; Yuningsih (Shofanah Media Berkah, 2024)
This study aims to determine the effect of psychological well-being and psychological contracts on work engagement of employees of Perum DAMRI Lampung branch. The sample of this study was 151 respondents. This study is a quantitative study and the sampling method used probability sampling with simple random sampling technique. Analysis of each variable using instrument test tools including validity test, reliability test, normality test, multiple linear regression analysis, and partial t-test processed with SPSS 25. This study supports the proposed hypothesis. So, the results of this study indicate that the psychological well-being variable and the psychological contract variable have a positive and significant effect on work engagement. The conclusion is that the higher the psychological well-being and psychological contract established between employees and the company, the higher the employee's work engagement. Based on the findings of this study, it is expected that company leaders can provide and develop award programs, career development, work schedule flexibility, and employees are expected to manage stress and work enthusiasm by carrying out positive activities.